1990
DOI: 10.1164/ajrccm/142.3.571
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Salmeterol and Salbutamol in Asthmatic Patients: An Evaluation of Asthma Symptoms and the Possible Development of Tachyphylaxis

Abstract: Salmeterol (SM) is a new beta 2-adrenoceptor agonist for inhaled use that has been shown to produce long-lasting bronchodilation in asthmatic patients. In the present study, evaluating efficacy and possible development of tachyphylaxis after SM, 12 patients with stable asthma were included after the demonstration of reversibility in FEV1 of at least 15% to 200 micrograms salbutamol (SB) or 20% to 500 micrograms SB. At inclusion all patients were receiving treatment with inhaled beta 2-agonists, and 11 of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
53
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 2 publications
3
53
0
Order By: Relevance
“…Extensive clinical trial data have been obtained with these drugs, which indicate that they both cause significant bronchodilation for at least 12 h after a single administration [1][2][3][4][5]. Both compounds are well-tolerated and highly potent; the principal difference in their clinical pharmacology being the faster onset of action of formoterol compared to salmeterol [6][7][8]. The extended duration of action of formoterol and salmeterol, which greatly exceeds that of more familiar beta 2 -adrenoceptor agonists, such as salbutamol and terbutaline, has prompted considerable debate on the underlying mechanism(s).…”
mentioning
confidence: 99%
“…Extensive clinical trial data have been obtained with these drugs, which indicate that they both cause significant bronchodilation for at least 12 h after a single administration [1][2][3][4][5]. Both compounds are well-tolerated and highly potent; the principal difference in their clinical pharmacology being the faster onset of action of formoterol compared to salmeterol [6][7][8]. The extended duration of action of formoterol and salmeterol, which greatly exceeds that of more familiar beta 2 -adrenoceptor agonists, such as salbutamol and terbutaline, has prompted considerable debate on the underlying mechanism(s).…”
mentioning
confidence: 99%
“…Treatment ranging from 2 weeks to 12 months with salmeterol 50 µg b.d. has also demonstrated that responsiveness to inhaled salbutamol was not decreased during or after treatment, suggesting no change in β 2 -receptor sensitivity [8,9] Other published data have, conversely, reported that 4 weeks of treatment with the long-acting β 2 -agonist formoterol, results in tolerance to its acute bronchodilator effects [10] and a recently published study has claimed that continuous exposure to salmeterol 50 µg b.d. results in reduced bronchodilator response to repeated doses of inhaled salbutamol [11].…”
mentioning
confidence: 99%
“…Inhaled β 2 -agonists have become the treatment of choice in acute asthma because of their excellent bronchodilating effects [1,2]. In recent years however, the regular use of short-acting inhaled β 2 -agonists for the treatment of asthma has been controversial, with reports of worsening of asthma control, a desensitization of β 2 -receptors and rebound increases in bronchial hyperresponsiveness [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic use does not appear to lead to tachyphylaxis to its bronchodilator effects [13]. However, CHEUNG et al [14] found that regular treatment with salmeterol in mild asthmatics led to significant tolerance to its bronchoprotective effects against methacholine challenge [14].…”
mentioning
confidence: 99%